Exploring the making of a galactic wind in the starbursting dwarf irregular galaxy IC 10 with LOFAR. Issue 2 (9th February 2018) - Heesen, V; Rafferty, D A; Horneffer, A; Beck, R; Basu, A; Westcott, J; Hindson, L; Brinks, E; Chyży, K T; Scaife, A M M; Brüggen, M; Heald, G; et al.
Abstract: Low-mass galaxies are subject to strong galactic outflows, in which cosmic rays may play an important role; they can be best traced with low-frequency radio continuum observations, which are less affected by spectral ageing. We present a study of the nearby starburst dwarf irregular galaxy IC 10 using observations at 140 MHz with the Low-Frequency Array (LOFAR), at 1580 MHz with the Very Large Array (VLA), and at 6200 MHz with the VLA and the 100-m Effelsberg telescope. We find that IC 10 has a low-frequency radio halo, which manifests itself as a second component (thick disc) in the minor axis profiles of the non-thermal radio continuum emission at 140 and 1580 MHz. These profiles are then fitted with 1D cosmic ray transport models for pure diffusion and advection. We find that a diffusion model fits best, with a diffusion coefficient of D  = (0.4–0.8) × 10 26 ( E /GeV) 0.5  cm 2  s −1, which is at least an order of magnitude smaller than estimates both from anisotropic diffusion and the diffusion length. In contrast, advection models, which cannot be ruled out due to the mild inclination, while providing poorer fits, result in advection speeds close to the escape velocity of ≈ 50 km s − 1, as expected for a cosmic ray-driven wind. Our favoured model with an accelerating wind provides a self-consistent solution, where the magnetic field is in energy equipartition with both the warm neutral and warm ionized medium with an important contribution from cosmic rays. Consequently, cosmic rays can play a vital role for the launching of galactic winds in the disc–halo interface.